FOOD AND BEVERAGE CONTROL IN SELECTED 2-5 STAR HOTELS IN NAIROBI, KENYA. - Gesage, Bichage M. (IJRDO - Journal of Applied Management Science, 2017)
The purpose of the study was to determine the types of cost control measures operational in 2 – 5 star hotels and establish if these measures were effective in keeping the cost of sales within acceptable limits. The study was carried in 2-5 star hotels within Nairobi province. Nine hotels were studied. Measures of independence including Chi-square tests were used to highlight whether significant associations between were different variables. Analysis of variance was performed to test if there were significant differences between the actual and standard food and beverage cost. The results revealed that there were significant differences between actual and standard beverage costs amongst all the star hotel categories. There were equally significant differences between the actual and standard/target food cost targets. The mean standard beverage costs between the various hotel star categories were significant at 95% confidence level. Higher star rated hotels were more likely to meet their food and beverage costs than their lower rated counterparts because there was a significant association between the hotel star category and the likelihood of meeting the food and beverage cost targets. Higher rated hotels did not have a serious costs side problem and could make more profits by giving more attention to the demand side, by encouraging more people to consume their services. Lower ranked hotels appeared to have cost side problems. Therefore more profits can be realized by these hotels if they institute more stringent cost control measures.